Low-Cost RFID Identification Variation - Lin, K.; Yeh, T.; Liu, Y.; Lin, Chad (Atlantis Press, 2006)
Interests continue to grow in recent years for the adoption of Radio Frequency Identification (RFID) in many different areas including transportation and supply chain management. Those RFID-included objects can be targeted more efficiently by real-time tracking and instant management. However, because of the contact-less type of RFID remote retrieval, the transmission of data in the air is very vulnerable to eavesdropping or appropriation. A primary security concern surrounding RFID technology is the illicit tracking of consumer location and analyzing of their shopping habits or behavior. This paper proposes a more secure and lightweight RFID variation protection protocol which enhances the security of the transmission of information as well as the consumer privacy protection by using randomized control access and two-way identification. In addition, this protocol also improves the overall performance and lowers the cost of RFID tag without any complicated calculation.